2011
DOI: 10.1108/14636691111146154
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of switching behavior in the Thai cellular market

Abstract: Purpose -The purpose of this paper is to explain the determinant factors of switching behavior in the Thai cellular market before the Mobile Number Portability (MNP) policy is implemented.Design/methodology/approach -A binary logit model and individual survey data from the National Telecommunications Commission 2009 are used to estimate the intention of mobile phone consumers to switch.Findings -The results show that subscriber characteristics, including age, government officer, self-employed, internet use, ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
0
5
0
2
Order By: Relevance
“…The Supreme Administrative Court has decreed that the NTC does not have the authority to issue the 3G licence. The National Broadcasting and Telecommunications Commission (NBTC) or a new regulatory body needs to be formed to oversee the matter, due to the 2007 Constitution(Srinuan et al, 2011a,…”
mentioning
confidence: 99%
“…The Supreme Administrative Court has decreed that the NTC does not have the authority to issue the 3G licence. The National Broadcasting and Telecommunications Commission (NBTC) or a new regulatory body needs to be formed to oversee the matter, due to the 2007 Constitution(Srinuan et al, 2011a,…”
mentioning
confidence: 99%
“…Hence, to overcome the potential bias in results due to model misspecification (Jarvis, MacKenzie, & Podsakoff, 2003), our study operationalised the SERVQUAL Model as a formative-reflective construct (details are given in measures section). The existing body of knowledge on loyalty has shown that perceived service quality is an important building block for improving business performance, especially in the long run, to reduce churn and eventually gain loyalty (Alnsour, Abu Tayeh, & Alzyadat, 2014;Hong & Lee, 2018;Izogo & Ogba, 2015;Johnson & Sirikit, 2002;Premkumar & Rajan, 2017;Santouridis & Trivellas, 2010;Srinuan, Tsani Annafari, & Bohlin, 2011). Hence, the following hypothesis is proposed: H1: Perceived service quality has a positive effect on customer loyalty.…”
Section: Perceived Service Quality and Customer Loyaltymentioning
confidence: 99%
“…Pesaing dalam dunia pemasaran adalah salah satu yang harus difikirkan oleh perusahaan [4]. Persaingan menjadi sengit ketika pesaing mengambil alih pelanggan setia kita [5]. Banyaknya perusahaan yang banyak di tawarkan di pasar mengakibatkan pelanggan akan beralih merek atau yang disebut "Customer Swtiching Behavior" [6].…”
Section: Pendahuluanunclassified
“…Perilaku perpindahan pelanggan pada penelitian terdahulu ditemukan pada industri telekomunikasi yang berkaitan dengan penyedia provider yang memiliki banyak faktor yang berdampak pada perilaku perpindahan pelanggan [5]. Penelitian customer switching behavior pun ditemuka pada industri perhotelan (Dev, Zhou, Brown, & Agarwal, 2009).…”
Section: Pendahuluanunclassified